Natural fibres for geotextiles - de Souza, Sivoney Ferreira; Cherian, Bibin Mathew [UNESP]; Leão, Alcides Lopes [UNESP]; Kozłowski, Ryszard M.; Thomas, Sabu (Elsevier, 2020)
Geotextiles prepared with natural fibres are an emerging technology with versatile applications. The differential is their intrinsic features such as renewability, biodegradability, biocompatibility, lower cost and carbon footprint compared to the traditional materials. In the present chapter, key properties are addressed. Many aspects of the main geotextiles are described including chemical composition, physical structure and types of mats according to its functional need. Also, the possibility of using different designs, shapes, composition due to the versatile range of natural fibre sources, can promote great interactions with the soil, it can helps to delay crack development in asphalt, the restraint of soil through filtration and drainage when the filter cake is formed; it can control the erosion and helps the vegetative growth; reinforcement of civil construction in pavement and rail road; and others. Technical aspects, construction processes and long-term durability are described and the perspectives to develop this supply chain.
Keywords: Biodegradability; Chemical composition; Lignin protection; Natural fibres; Reinforcement